Expert Perspectives on Hereditary Angioedema: Key Areas for Advancements in Care across the Patient Journey. Issue 3 (September 2016) - Banerji, Aleena; Baş, Murat; Bernstein, Jonathan A.; Boccon-Gibod, Isabelle; Bova, Maria; Dempster, John; Grumach, Anete Sevciovic; Magerl, Markus; Poarch, Kimberly; Ferreira, Manuel Branco
Background: Published literature documents the substantial burden of hereditary angioedema (HAE) with C1 inhibitor deficiency on the quality of life and work productivity of patients. However, despite advances in the field and the availability of guidelines to advise health care providers (HCP) on the diagnosis and management of HAE, there are still many challenges to overcome. For example, delayed diagnosis and misdiagnosis are common, and treatment practices vary worldwide. Objective: An international expert panel was convened to consider opportunities for improvements that would benefit patients with HAE. Methods: Based on professional and personal experiences, the experts developed schematics to describe the journey of patients through the following stages: (1) onset of symptoms and initial evaluation; (2) referral/diagnosis; and (3) management of HAE. More importantly, the panel identified key areas in which it was possible to optimize the support provided to patients and HCPs along this journey. Results: Overall, this approach highlighted the need for wider dissemination of algorithms and scientific data to more effectively educate HCPs from multiple disciplines and the need for more research to inform appropriate treatment decisions. Furthermore, HAE awareness campaigns, accurate online information, and referral to patient advocacy groups were all considered helpful approaches to support patients. Conclusion: More detailed and widespread information on the diagnosis and management of HAE is needed and may lead to advancements in care throughout the journey of the patient with HAE.